A contribution to the phylogeny and taxonomy of the Pachydactylus weberi group (Squamata: Gekkonidae): a case of intraspecific colour polymorphism confounding taxonomy. Issue 2 (3rd July 2018) - Šmíd, Jiří; Engelbrecht, Hanlie; Taft, Jody M.; Telford, Nicolas S.; Makhubo, Buyisile G.; Bauer, Aaron M.; Tolley, Krystal A.
ABSTRACT: Pachydactylus is the most species-rich reptile genus in southern Africa. Most species are habitat specialists adapted to hyper-arid conditions of the Namibian and north-western South African xeric regions. Although a fair number of phylogenetic studies and taxonomic revisions have been published, some species still remain rather enigmatic. In the ten years since the taxonomic revision of the weberi group, some of the species have not been recorded and our knowledge on their distribution, phylogenetic affinities, or intraspecific variability is limited or non-existent. Pachydactylus goodi is one such species. In this study, we report a newly discovered population of P. goodi in the Richtersveld National Park, South Africa, which considerably extends the known range of the species. In addition, the results of our phylogenetic analyses indicate that P. goodi is paraphyletic with respect to P. atorquatus . Although there is a striking colour polymorphism observed between these two species, the level of genetic differentiation within the goodi-atorquatus clade is comparable with intraspecific variability observed in other Pachydactylus species. As a result of these findings, which are further supported by morphological similarity of the two species, we conclude that they represent a single species and synonymise P. goodi with P. atorquatus .